2018
DOI: 10.3390/ijms19051543
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled Receptors as Potential Therapeutic Targets in Human Cancers

Abstract: Frizzled receptors (FZDs) are a family of seven-span transmembrane receptors with hallmarks of G protein-coupled receptors (GPCRs) that serve as receptors for secreted Wingless-type (WNT) ligands in the WNT signaling pathway. Functionally, FZDs play crucial roles in regulating cell polarity, embryonic development, cell proliferation, formation of neural synapses, and many other processes in developing and adult organisms. In this review, we will introduce the basic structural features and review the biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 108 publications
1
79
1
Order By: Relevance
“…With the exception of FZD5, other FZDs, including FZD3, FZD4, FZD8, and especially FZD9, can also significantly promote LRP5/␤-catenin signaling in a ligand-independent manner. Because ectopic expression of FZDs in tumor cells is a common phenomenon (34,35), these findings may provide an alternative mechanism to comprehensively understand the molecular basis underlying tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of FZD5, other FZDs, including FZD3, FZD4, FZD8, and especially FZD9, can also significantly promote LRP5/␤-catenin signaling in a ligand-independent manner. Because ectopic expression of FZDs in tumor cells is a common phenomenon (34,35), these findings may provide an alternative mechanism to comprehensively understand the molecular basis underlying tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…6H), implying that the endogenous canonical WNT glycoproteins were not involved in suppressing GSK3␤-AXIN-APC complexes. Therefore, we concluded that ectopic expression of Frizzled receptors (34,35), such as FZD3/4/5/9, which cause ligand-independent LRP5/6 signalosome activation, might be the putative pathological factor for the constitutive activation of WNT/␤-catenin signaling in HepG2 cells.…”
Section: Ligand-independent Fzd-lrp5/6 Signaling May Be Involved In Tmentioning
confidence: 92%
“…The functions of WNT ligands, which bind to the frizzled family of seven transmembrane receptors ( Zeng et al, 2018 ), are modulated by FGF10 signaling during stomach ( Nyeng et al, 2007 ) and lung ( Volckaert and De Langhe, 2015 ) development. FGF10 also regulates Bone Morphogenetic Protein 4 (BMP4) during lung branching ( Weaver et al, 2000 ).…”
Section: Fgf10-dependent Regulators Of Intracellular Signalingmentioning
confidence: 99%
“…Genetic or pharmacological inhibition of elements of the Wnt/Fzd pathway (Fzd4, LRP-5, Dishevelled, and β-catenin) impairs retinal NV and vascular permeability. [24][25][26] Recent studies have demonstrated that the anti-Fzd7 antibody [27][28][29][30] antagonized Wnt/β-catenin signaling in Fzd7-expressing cancer cells, and suppressed tumor progression and metastasis. 21,22 Dysregulation of Wnt signaling is also associated with ocular diseases with an emphasis on DR. 23 Previously, we have demonstrated that Frizzled-7 (Fzd7) signaling controls post natal vessel formation in the retina, 20 however its role in pathological angiogenesis is still unknown.…”
Section: Introductionmentioning
confidence: 99%